Vaping and e-cigarette's as a danger of 21st century - overview of the lately reported side effects - Paula Bieganek; Michał Tokarski; Angelika Tokarska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Vaping devices have gained popularity among youth and young adults due to their appealing flavors and the perception that they are less harmful than traditional tobacco cigarette's. However, emerging evidence suggests that vaping may expose users to high level of hazardous chemicals, potentially leading to severe lung injuries and other side effects. The purpose of this review is to look closely to the dangers. The aim of this review is to look closely at the various side effects of vaping and usage of e-cigarette's. Materials and methods: This article is a literature review based on publications from PubMed and Cochrane Library, keywords included: vaping; e-cigarette's; cardiovascular effect; pulmonary effect; oral health. The state of knowledge: Smoking is a major contributor to cardiovascular disease (CVD), including atrial fibrillation (AF) and venous thromboembolism (VTE). People who currently smoke have an increased rate of hospitalization for heart failure (HF). The surge in vaping and e-cigarette use has resulted in an epidemic of hospitalizations and fatalities among e-cigarette users due to acute lung injury, a newly identified condition known as e-cigarette or vaping use-associated lung injury (EVALI). Beside cardiovascular and pulmonary effects vaping and e-cigarette's are linked to various immediate and long-term health hazards. Conclusions: Vaping poses significant health risks, particularly for young people. Side effects include respiratory problems, cardiovascular issues, and an increased risk of nicotine addiction. Additionally, exposure to harmful chemicals in e-cigarette aerosols can lead to long-term health complications. Despite its popularity as a safer alternative to smoking, the negative impacts of vaping are substantial and warrant serious attention and preventive measures. Key words: vaping; e-cigarett's; cardiovascular effect,;pulmonary effects; oral health